2022
DOI: 10.1108/nbri-06-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Green purchasing behaviour of international tourists in Malaysia using green marketing tools: theory of planned behaviour perspective

Abstract: Purpose This study aims to examine the effects of green marketing tools on tourists’ behavioural intention to buy green products by measuring individuals’ subjective norms, attitudes and perceived behavioural control. Design/methodology/approach A total of 421 international tourists from several tourist attractions in Malaysia, selected through convenience sampling, participated in a survey. Findings The analysis results using partial least squares structural equation modelling suggest that behavioural int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 86 publications
1
29
0
1
Order By: Relevance
“…When it comes to buying green products, consumers who have better long-term environmental knowledge are more likely to spend more money and be more eager (Brosdahl and Carpenter, 2010). This finding also corresponds with previous studies that reported that having sufficient information about environmental issues and being responsible for the environment will cultivate consumers’ ecocentric attitudes while considering the behavioural intention of choosing green hotels (Paco and Lavrador, 2017; Patwary et al , 2022; Rahman and Reynolds, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…When it comes to buying green products, consumers who have better long-term environmental knowledge are more likely to spend more money and be more eager (Brosdahl and Carpenter, 2010). This finding also corresponds with previous studies that reported that having sufficient information about environmental issues and being responsible for the environment will cultivate consumers’ ecocentric attitudes while considering the behavioural intention of choosing green hotels (Paco and Lavrador, 2017; Patwary et al , 2022; Rahman and Reynolds, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, the concept of event quality is critical to research on event tourism and event participants' behavior as it predicts satisfaction, behavioral intention or loyalty (Patwary et al , 2021; Armbrecht, 2021; Lee and Beeler, 2009; Yoon et al , 2010). Event quality derives from the literature in services marketing related to service quality (Shonk et al , 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Social exchange theory states that residents who have a favourable view of tourism are more likely to participate in tourist-related activities. When citizens know that they would benefit from tourism without incurring extra costs, they will be more inclined to engage and contribute to community-based tourism development initiatives (Lo and Janta, 2020;Patwary et al, 2022). According to the research on tourism, the host-to-tourist interactions and their outcomes have received insufficient attention (Eusébio et al, 2018).…”
Section: Host Tourists Interaction and Resident Welcoming Attitudementioning
confidence: 99%